Source apportionment of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Palm Beach County, Florida. (2nd April 2016) - Afshar-Mohajer, Nima; Wilson, Christina; Wu, Chang-Yu; Stormer, James E.
ABSTRACT: Due to concerns about adverse health effects associated with inhalation of atmospheric polycyclic aromatic hydrocarbons (PAHs), 30 ambient air samples were obtained at an air quality monitoring station in Palm Beach County, Florida, from March 2013 to March 2014. The ambient PAH concentration measurements and fractional emission rates of known sources were incorporated into a chemical mass balance model, CMB8.2, developed by EPA, to apportion contributions of three major PAH sources including preharvest sugarcane burning, mobile vehicles, and wildland fires. Strong association between the number of benzene rings and source contribution was found, and mobile vehicles were identified to be the prevailing source (contribution ≥56%) for the observed PAHs concentration with lower molecular weights (four or fewer benzene rings) throughout the year. Preharvest sugarcane burning was the primary contributing source for PAHs with relatively higher molecular weights (five or more benzene rings) during the sugarcane burning season (from October to May of the next year). Source contribution of wildland fires varied among PAH compounds but was consistently lower than for sugarcane burning during the sugarcane harvest season. Determining the major sources responsible for ground-level PAHs serves as a tool to improving management strategies for PAH emitting sources and a step toward better protection of the health of residents in terms of exposure to PAHs. The results obtain insight into temporal dominance of PAH polluting sources for those residential areas located near sugarcane burning facilities and have implications beyond Palm Beach County, in areas with high concerns of PAHs and their linked sources. Implications : Source apportionment of atmospheric polycyclic hydrocarbons (PAHs) in Palm Beach County, Florida, meant to estimate contributions of major sources in PAH concentrations measured at Belle Glade City of Palm Beach County. Number of benzene rings was found to be the key parameter in determining the source with the prevailing contribution. Mobile vehicle sources showed a higher contribution for species with four or fewer benzene rings, whereas sugarcane burning contributed more for species with five or more benzene rings. Results from this study encourage more control for sugarcane burns and help to better manage authorization of the sugarcane burning incidents and more restrictive transportation plans to limit PAH emissions from mobile vehicles.